Pengaruh Jam Terbang Pemain Bulu Tangkis Women Single Terhadap Ranking Dunia Di Jumlah Poin Menggunakan Regresi Linear Sederhana - Shendy Rizki Pradana Shendy (Jurnal Riset Informatika dan Teknologi Informasi, 2026)
This study aims to analyze the relationship between playing time and age in badminton players and their world rankings using simple linear regression. Data were collected from women's singles badminton players ranked 1-100, including information on their rankings based on points and playing time. Simple linear regression analysis was used to understand the extent of the linear relationship between the two variables. The analysis results indicate a correlation between playing time and points earned. Regression coefficients and statistical significance are discussed to gauge the strength and relevance of this relationship. The findings of this study provide deeper insight into factors that may influence badminton player performance, with a focus on playing time. The discussion includes interpretation of the results, implications in the context of badminton, and potential managerial or coaching implications. Limitations of the study and directions for future research are also discussed. This study is expected to contribute to the understanding of factors influencing badminton players' world rankings.